Kinetic index combining native and postcontrast myocardial T1 in hypertrophic cardiomyopathy. Issue 6 (15th May 2015) - Kachenoura, Nadjia; Besson‐Hajji, Laila; Graves, Martin J; Reid, Scott; Soulat, Gilles; Ashrafpoor, Golmehr; De Cesare, Alain; Hagege, Albert; Redheuil, Alban; Mousseaux, Elie
Abstract : Background: To evaluate ability of pre‐ and postcontrast apparent T1* indices, as well as their combination to characterize myocardial structural changes in hypertrophic cardiomyopathy (HCM). Methods: Study protocol was approved by institutional review board and informed consent was obtained. T1 mapping was performed using MOLLI sequence (1.5T magnet) on: (i) tubes with known T1 and varied heart‐rates (HR), (ii) 17 HCM (55 ± 15 years) and 18 controls (49 ± 16 years), before contrast and every 5 min over 20 min postcontrast. Global and segmental native T1 (T1*Native ), extracellular volume (ECV) and percentage of decrease in myocardial T1* (T1*decay = 100·[1‐T1*Post‐contrast /T1*Native ]) were estimated. Correlation coefficients of associations between T1 and LV indices, such as left ventricular wall thickness (WT) and mass index (LVMi) were provided. Receiver operator curve analysis was performed on per‐patient basis to assess ability of T1* indices to identify HCM. Results: While up to a T1* of 1000 ms the effect of HR was minor, it was more pronounced above 1000 ms. T1*Native (754 ± 76 ms versus 1014 ± 130 ms, P < 0.001), ECV20min (23 ± 5% versus 27 ± 4%, P = 0.005), and T1*decay5, 10, 15 or 20min (38 ± 8% versus 54 ± 6%, P < 0.001) showed significant differences between controls and HCM. Correlation coefficients for associations with WT and LVMi were higher for T1*Native and T1decay, independent of acquisition time (with WT/LVMi: r = 0.58/0.44 ( P < 0.05) for T1*Native ; r = 0.23 ( P < 0.05)/0.23 for ECV20min ; r > 0.51/ > 0.45( P < 0.05) for T1*decay5, 20min ). T1*Native (97.1%) and T1*decay (91.2%) characterized HCM with higher accuracy ( P < 0.02) than ECV (69%). Conclusion: T1*Native and T1*decay were able to characterize HCM more accurately than ECV, even in the absence of myocardial hypertrophy and late‐gadolinium enhancement. J. MAGN. RESON. IMAGING 2015;42:1713–1722.